Polycythemia Vera in Pregnancy: A Descriptive Review of the Literature - Nicole Xu; Bernard Gonik (IMR Press, 2023)
Objectives: Polycythemia vera (PV) is a rare myeloproliferative neoplasm that is associated with a high risk of thrombosis due to an increase in red blood cell mass and hyperviscosity. In the setting of pregnancy, patients with PV appear to be at even higher risk for a variety of pregnancy-related thrombotic and other adverse outcomes. While a diagnosis of PV is relatively uncommon in younger reproductive age women, as mean maternal age at first birth increases, incidence of pregnancies complicated due to PV may also increase in the future. Mechanism: A review of the literature was conducted using the PubMed database and relevant search keywords (MeSH terms) "polycythemia" AND "pregnancy". Findings in Brief: PV must be differentiated from other primary, secondary, and relative causes of polycythemia. A bone marrow biopsy is typically used to confirm the diagnosis. Most, but not all patients with PV, are identified to have a somatic mutation in the JAK2 gene. In pregnancy, the mainstay interventions are serial phlebotomies to maintain the hematocrit in an appropriate range and daily low dose aspirin therapy. Low molecular weight heparin is added for pregnant patients thought to be at additional risk for thrombosis. For resistant cases, the use of interferon alpha has been advocated for cytoreductive therapy. Conclusions: Based on very limited data, these interventions have been reported to improve pregnancy outcomes. Although hydroxyurea is considered a first-line treatment for PV, it is contraindicated in pregnancy due to concerns for teratogenicity. There are a number of newer agents that have been utilized to treat PV and other myeloproliferative neoplasms in nonpregnant individuals. None of these agents have been adequately studied in pregnancy to allow support for their use except perhaps under extraordinary circumstances and with appropriate informed consent.